"How Do You Know If It Is Love or Lust?" On Gender, Status, and Violence in Old Norse Literature (Interfaces: A Journal of Medieval European Literatures, 2016)
This article examines attitudes towards behaviour relating to women within Old Norse literature, focusing both on chivalric romances (translated and original, the riddarasögur) and the legendary sagas (fornaldarsögur), texts that were mostly written in the thirteenth and fourteenth centuries. The written chivalric romances arrived in Iceland from Norway and southern Europe, and thus they often exhibit different values from those found in the fornaldarsögur, which tend to reflect indigenous Nordic and heroic storytelling traditions. The article explores differences between the two traditions regarding male emotions and attitudes towards women, with an emphasis on texts in which women are abused. In particular, the article seeks to investigate the relationship between social status and gender roles in these texts, and whether a woman's rank affects her role and status according to gender. It focuses particularly on romances (especially those featuring courtly love) and fornaldarsögur in which women are either idealised as goddesses, or mistreated and even sexually abused because of their gender. The article concludes by asking how far the contrasts within the texts reflect a Norse 'emotional community,' as compared with continental European values, and whether these textual differences reflect actual difference in the social expressions of emotional behaviour.
Keywords: Old Norse; Medieval literature; violence; social status; gender